Options in tourism development: Concious versus conventional tourism - Andriotis, Konstantinos (My University, 2002)
Development by its nature is a process of change that may be implemented in a variety of ways. As a result, tourist receiving destinations have a variety of options to follow in developing their tourism industry. These options concern mainly the process and/or funding of development, and include the following dichotomous alternatives: capital versus labour intensive; endogenous versus exogenous; small scale versus large; alternative versus mass and enclave versus spread out. It is the aim of this paper to discuss the five alternatives by undertaking a literature review to investigate the benefits and costs associated with each of them and providing guidelines for destination tourism development. From the review it is evident the possibility of categorising the five development options into two distinctive groups, namely conscious and conventional tourism. Each group presents differences to its impacts to a tourist receiving destination, the ownership/control patterns of the industry and the numbers of facilities and tourists.
Keywords: Conscious tourism; Conventional tourism; Development options